ANTIDEPRESSANT POTENTIAL OF ISOLATED BIOACTIVE COMPOUND FROM BUTEA MONOSPERMA (LAM.) KUNTZE - Kumar, Das; Mitra, Mazumder; Saumya , Das; Sanjita, Das (LIFE: International Journal of Health and Life-Sciences, 2017)
Traditional or alternative medicine refers other than orthodox medicine. From time immemorial, plants have been utilized as corrective agents for a variety of diseases. Butea monosperma (Lam.) Kuntze is a generally utilized plant in Ayurveda. Butea monosperma (Palas) has a place with the family Fabaceae, developed freely in many parts of India. Different phytochemical constituents present are carbohydrates, alkaloids, tannins, flavonoids, steroids and terpenoids. Butea monosperma is traditionally utilized as a free radical scavenger, antistress, CNS stimulant, antigout, diuretic, antileprotic, anti-inflammatory, antiulcer, astringent and antihepatotoxic. Its flower is utilized to treat instances of expanded spleen, menstrual aggravations, consuming sensations and eye diseases. Effect of Isolated bioactive compound from Methanol Extract of Butea monosperma (Lam.) Kuntze (BMME) was studied for the duration of immobility by Forced Swim Test (FST) At the dose of 20 mg/kg isolated compound showedsignificant effect (p<0.05) forduration of immobilitywhen compared with control group of animals. The monoamines are determined in mice brain to find out the altered levels of monoamines. It had been suggested that an increase in both swimming and climbing behaviors in the FST occurs when the animal is treated by a drug which increases NA and DA levels in the nerve terminals. An increase in NA and DA could be by inhibition of MAO activity in the brain.